Medical chemistry of nano disperse silica - Chuiko, A. A.; Pogorelyi, V. K. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2006)
As a result of the complex physico-chemical and medico-biological studies conducted by the Institute of Surface Chemistry of the NAS of Ukraine together with a number of research Institutes and clinics of the Ministry of Public Health of Ukraine, a new enterosorbent Silics has been developed and introduced into medicinal practice. This synthetic high disperse silica with an extended specific surface is characterized by its chemical purity, stability and physintroduced innocence. The regular structure of its surface as well as the presence of a large number of surface reactive sites insure a high adsorptive capacity of Silics with respect to water, protein molecules and toxins, pathogenic microorganisms and viruses. At present new technologies are being described for applications of Silics as an individual medicinal preparation of sorptive active and as active basis for a novel generation of composite drugs.